Ivo Andrić 1892-1992 - Thiergen, Peter (Vortraege und Abhandlungen zur Slavistik, 1995)
In 1961, exactly 50 years after his literary debut in the Bosanska vila, Ivo Andrić received the Nobel Prize for Literature. He was included in the literary pantheon. Some still call him "South Slav Tolstoy".